Peran Ilmu Bimbingan dan Konseling dalam Perspektif Filsafat - Harlina, Desi; Jamaris; Solfema (Universitas Nusantara PGRI Kediri, 2022)
Guidance and counseling as a science that is rooted in philosophy. Knowledge in guidance and counseling is defined as the study of regular and systematic processes, procedures or steps to assist individuals (clients) in improving themselves, overcoming problems and achieving other specific goals. The process of human science is a process to seek the truth and obtain knowledge. Likewise knowledge in guidance and counseling, can be seen based on the role of science as a scientific activity carried out by the scientific method and then proven systematically.